The limits of globalization : cases and arguments - Scott, Alan, 1956- (Routledge, 1997)
This book examines the concrete manifestations of the globalizing forces operating in the world today. It unpicks the rhetoric of globalization in political analysis, cultural theory and urban and economic sociology.
Keywords: International economic relations -- Social aspects.; International relations -- Social aspects.; Cultural relations.; Intercultural communication.; Internationalism.; International economic relations -- Case studies.; Globalization.; Relations économiques internationales -- Aspect social.; Relations internationales -- Aspect social.; Relations culturelles.; Communication interculturelle.; Internationalisme.; Relations économiques internationales -- Cas, Études de.; Mondialisation.; internationalism.; globalism.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; Cultural relations; Globalization; Intercultural communication; International economic relations; International economic relations -- Social aspects; International relations -- Social aspects; Internationalism; Electronic books.; Case studies